THE EFFECT OF IMPROVING QUALITY OF SPORTS PHYSIOLOGY - SUKIRNO, SUKIRNO (Sriwijaya University Learning and Education International Conference, 2016)
Sport is a human activity that is reasonable in accordance with the divine nature aims to providewelfare for those who do. Welfare highest is health. Healthy physical and spiritual. Therefore thisarticle aims to explain the role of sport and its effect on improving the quality of physiology,which relates to the quality of physical health. This paper uses the method of literature, related tosports and physiology. Based on the results of the various opinions, it can be concluded, that sportsactivities are carried out regularly and continuously, through stages that are tailored to the abilitiesof individuals, will directly improve the quality of physiology, especially the performance of theheart, lungs, associated with the use oxygen in the lungs, including body fluids, such as red bloodcirculation, the function of white blood, and platelets.